Assessment of sensory neuropathy in patients with diabetic foot problems - Nather, Aziz (Co-Action Publishing, 2011)
Our aim of this study was to compare the accuracy of three different modalities for testing sensory neuropathy in diabetic patients with and without diabetic foot problems. The three devices used included the pin-prick testing using the Neurotip® (PPT), the Semmes–Weinstein 5.07/10 g monofilament testing (SWMT), and the rapid-current perception threshold (R-CPT) measurements using the Neurometer® testing. Our study population consisted of 54 patients (108 feet) with diabetic foot problems treated at the National University Hospital in Singapore by our multi-disciplinary diabetic foot care team. Our results showed no difference in sensory neuropathy detected by PPT and 5.07/10 g SWMT in both the pathological and normal foot. In the pathological foot, there was significant increase in sensory neuropathy detected by the Neurometer® device at both the big toe and ankle sites as compared to PPT and 5.07/10 g SWMT. In the normal foot, there was a significant increase in sensory neuropathy detected by the Neurometer® device at the big toe site only as compared to PPT and 5.07/10 g SWMT. Finally, the Neurometer® measurements detected a statistically higher proportion of feet with sensory neuropathy as compared to detection by the PPT or 5.07/10 g SWMT.